2019
DOI: 10.4171/ggd/526
|View full text |Cite
|
Sign up to set email alerts
|

Big Torelli groups: generation and commensuration

Abstract: For any surface Σ of infinite topological type, we study the Torelli subgroup I(Σ) of the mapping class group MCG(Σ), whose elements are those mapping classes that act trivially on the homology of Σ. Our first result asserts that I(Σ) is topologically generated by the subgroup of MCG(Σ) consisting of those elements in the Torelli group which have compact support. In particular, using results of Birman [4], Powell [24], and Putman [25] we deduce that I(Σ) is topologically generated by separating twists and boun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Adapting an argument presented in [45,Theorem 7.16] showing that the mapping class group of a finite-type surface is generated by torsion elements, Afton-Freedman-Lanier-Yin [1] observed: Combining results of Birman [24], Powell [98] and an argument due to Justin Malestein, the above theorem implies the following (see [10] for details and definitions): Theorem 4.7 ( [10]). Let S be any surface of infinite type.…”
Section: Topological Generationmentioning
confidence: 93%
See 1 more Smart Citation
“…Adapting an argument presented in [45,Theorem 7.16] showing that the mapping class group of a finite-type surface is generated by torsion elements, Afton-Freedman-Lanier-Yin [1] observed: Combining results of Birman [24], Powell [98] and an argument due to Justin Malestein, the above theorem implies the following (see [10] for details and definitions): Theorem 4.7 ( [10]). Let S be any surface of infinite type.…”
Section: Topological Generationmentioning
confidence: 93%
“…In [10], it shown that I(S) is also algebraically rigid; more concretely: The equivalent statement for finite-type surfaces was proved by Farb-Ivanov [44] for automorphisms, and by Brendle-Margalit [27] for commensurations.…”
Section: 11mentioning
confidence: 97%
“…In [3] the authors found a topological generating set for I(S) when S is infinite type. Theorem 9.2 ([3], Corollary 2).…”
Section: Torelli Groupmentioning
confidence: 99%
“…Further developments, providing actions of Map(Σ) on hyperbolic graphs under various topological conditions on the surface, include [3,20,21], for instance. The study of the geometry of such graphs is still in constant expansion (see, e.g., [4,7,26]).…”
Section: Hyperbolic Actions and Nondisplaceable Subsurfacesmentioning
confidence: 99%